Intellectual property protection and the globalization of the world economy - Matthias Zeeb (Intereconomics, 1996)
The quest for technological leadership has caused the widespread use of intellectual property protection (IPP) as an instrument of national technology policies. Even the Agreement on Trade-Related Intellectual Property Rights (TRIPs) can be interpreted as an attempt to hinder the international diffusion of know-how from industrialized countries to technological followers. However, considering the globalization of the world economy, its effects might well be different from those expected.
Keywords: 330; Intellectual Property Rights